Control del cursor de un computador mediante eyetracking (2020)
People with conditions such as cerebral palsy have many limitations to carry out activities of daily life. For this reason, the present project proposes the realization of a program that allows to facilitate the interaction between computers and people with cerebral palsy. A convolutional neural network model was trained and used, also cascade image filters were necessary to predict the visual focus position on a computer screen to control the cursor using only the gaze.